In vitro antibacterial spectra and analysis of antimicrobal bioactive compound of Bacillus subtilis ASPL1 isolated from the soil of Ajodhya hill forest - Abhijit Mandal; Soumendranath Chatterjee (The Microbe)
Resurgence of infectious diseases and emergence of drug-resistant microbes is a significant threat to human health. Consequently, there is an urgent need for discovery of new antimicrobial drugs. Ecosystems like forest soil holds great promise for identification of bacterial strains capable to produce valuable natural products. In this study, we aimed to identify bioactive metabolites produced by the ASPL1 bacterial strain isolated from the rhizospheric soil of Ajodhya hill forest. Primary screening was focused on assessment of antibacterial properties of the ASPL1 against a range of pathogenic bacteria and the results demonstrated its broad-spectrum antimicrobial activity. Subsequently, secondary metabolites were extracted from the culture supernatant of the bacterium using ethyl acetate. Bioactivity of the crude extract was determined by plate diffusion method followed by LC-MS analysis. The extract exhibited significant inhibitory effects against the pathogenic strains viz Aeromonas caviae, Shigella flexneri, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis but Escherichia coli and fifteen bioactive compounds were identified some of which displayed antibacterial, antiviral, antifungal, anti-tumor, anti-cancer and antioxidant properties. Minimum inhibitory concentration (MIC) of the crude extract against various pathogens ranged from 128 to 512 μg/ml. Phylogenetic tree analysis based on 16S rRNA gene sequence identified the bacterial strain ASPL1 as Bacillus subtilis (OR335097). The study proved potential of B. subtilis ASPL1 (OR335097) as a valuable resource for bioactive secondary metabolites with antimicrobial activity for drug discovery. The findings underscored significance of Ajodhya hill forest as a source of diverse bacterial strains with various beneficial properties that can be harnessed for development of biological antibiotics.